Fibrous hamartoma of infancy in the scrotum - Report of a case - Naoki Hashizume; Kimio Asagiri; Naoko Komatsuzaki; Suguru Fukahori; Shinji Ishii; Nobuyuki Saikusa; Naruki Higashidate; Motomu Yoshida; Saki Sakamoto; Hirotomo Nakahara; Shinichiro Nakagawa; Yushi Abe; et al. (Elsevier, 2016)
Fibrous hamartomas of infancy (FHI) is rare benign tumors. FHI is typically present before the age of two years. We report a 13-month-old child with FHI, which presented as the growing scrotum mass clinically diagnosed rhabdomyosarcoma of the trunk. Right scrotal swelling was presented. The mass was irregular, solidly, and non-tender. Operative findings revealed a mass fixed to the scrotal fundus. FHI is differentiated from other malignant neoplasms in the scrotum.